2016
DOI: 10.1590/1806-9282.62.06.594
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus in childhood: an emerging condition in the 21st century

Abstract: Summary The International Diabetes Federation (IDF-2015) estimates the existence of 30,900 children under 15 years old with type 1 diabetes mellitus (DM1) in Brazil, and an increase of 3.0% per year is expected. This review focused on meta-analysis and pediatric diabetes update articles in order to draw attention to the need of planning coping strategies to support this serious public health problem in coming years. DM1 is considered an immuno-mediated disease with a complex transmission influenced by genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
0
5
0
2
Order By: Relevance
“…2 Many of the children and adolescents with type 1 diabetes are from low- and middle-income countries. 3 In Africa, type 1 diabetes among children and adolescents contributed to 166,400 cases in 2015, with 7,600 newly diagnosed children each year. 4 In Uganda, there is very limited information about the prevalence of type 1 diabetes among children and adolescents although anecdotal data from Mulago National Referral Hospital and Masaka Regional Referral Hospital – which are centers of childhood diabetes management in the central region of Uganda – indicate a rise in type 1 diabetes, which silently accounts for a high morbidity and a high mortality among people aged <18 years.…”
Section: Introductionmentioning
confidence: 99%
“…2 Many of the children and adolescents with type 1 diabetes are from low- and middle-income countries. 3 In Africa, type 1 diabetes among children and adolescents contributed to 166,400 cases in 2015, with 7,600 newly diagnosed children each year. 4 In Uganda, there is very limited information about the prevalence of type 1 diabetes among children and adolescents although anecdotal data from Mulago National Referral Hospital and Masaka Regional Referral Hospital – which are centers of childhood diabetes management in the central region of Uganda – indicate a rise in type 1 diabetes, which silently accounts for a high morbidity and a high mortality among people aged <18 years.…”
Section: Introductionmentioning
confidence: 99%
“…This fact results from a specific situation of our tertiary hospital, which is a reference center for the most common and severe endocrine, kidney, liver, and congenital diseases in Brazil. 14,16,25 Importantly, Psychiatry and Palliative and Pain Care were the medical areas in which the patient had a great chance of being followed by three or more medical specialties. This finding is related to the medical complexities in our critically ill patients, 25,26 who may also present several mental health conditions and chronic pain diseases.…”
Section: Discussionmentioning
confidence: 99%
“…12 The outcomes are distinct for these patients and need assessment of multiple specialties. [13][14][15][16][17][18][19][20] Recently, a study evaluated a large population of children and adolescents with PCDs followed in a Latin American tertiary hospital. The authors reported that patients required many appointments in multiple medical specialties and hospital admissions, especially in early adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Ainda, destaca-se que esta patologia influencia diretamente a qualidade de vida dos pacientes, assim como fatores aspectos sociodemográficos, psicossociais e familiares. Assim, é de suma importância o acompanhamento destes pacientes por equipe multiprofissional capacitada para instruir pacientes e familiares na autogestão e monitorização da DM [22][23][24].…”
Section: Discussionunclassified